Achievement of red blood cell transfusion independence in red blood cell transfusion-dependent patients with lower-risk non-del(5q) myelodysplastic syndromes correlates with serum erythropoietin levels. Issue 6 (11th May 2020) - Santini, Valeria; Almeida, Antonio; Giagounidis, Aristoteles; Skikne, Barry; Beach, CL; Weaver, Jerry; Tu, Nora; Fenaux, Pierre
Abstract: In the randomized, phase 3, MDS-005 study (NCT01029262), lenalidomide-induced red blood cell transfusion independence (RBC-TI) in 27% of transfusion-dependent patients with lower-risk non-del(5q) myelodysplastic syndromes (MDS) ineligible for or refractory to erythropoiesis-stimulating agents. To determine the influence of erythropoietin (EPO) level on response, 155 patients treated with lenalidomide in MDS-005 were categorized into four groups by baseline EPO level. The EPO >500 mU/mL group had higher RBC transfusion burden and the lowest proportion of patients with ring sideroblasts ≥15% versus lower EPO groups. Achievement of RBC-TI ≥8 weeks inversely correlated with EPO level, ranging from 42.5 to 15.5%. EPO level did not affect erythroid hematologic improvement response (36.2–44.4%). This analysis suggests patients with lower EPO levels experience the strongest benefit from lenalidomide. Although meaningful improvements were observed in some patients with EPO level >500 mU/mL, new treatments are needed for this population.